Assessing the relationship between technology, organization, environment as factors for big data adoption and organizational impact in Malaysia’s government linked agencies / Hasnah Hashim - Hashim, Hasnah (2023)
Big Data Adoption (BDA) is has been found to be effective in increasing the capacity of Malaysia’s Government-Linked Agencies (GLAs) since it offers better opportunities to be competitive through its insights. Even though data analytics are increasingly used by government and public sectors and around the world to enable decision process, however limited attention has been given from the research perspective and matter how it has been implemented in the Government-Linked Agencies, specifically in Malaysia. Started with massive data generated from various process from business activities, BD has great potential to exploit. BD have unique characteristics which able to trans format a lowest cost, reassure organization to gain significant meaning, valuable insights with the existing IT infrastructure in everyday operations.